ANALISIS KURVA RESESI ALIRAN DASAR MENGGUNAKAN MODEL RESERVOIR LINIER RECESSION CURVE HYDROOFFICE PADA DAS WURYANTORO KABUPATEN WONOGIRI PROPINSI JAWA TENGAH - Bokiraiya Okky Latuamury (Jurnal Teknosains, 2017)
The hydrograph recession curve expresses the theoretical relationship between the aquifer structure and the flow of groundwater flowing into the river basin channel. These theoretical relationships are often empirically depicted using the base flow recession curve. The hydrograph recession curve is commonly used to estimate the recessionary parameters, aquifer properties and to evaluate alternative hydrological hypotheses. The river basin hydrograph recession curve records the behavior of the relationship between the aquifer structure and its association with groundwater outflow to the river channel. This research was conducted with the aim: to analyze the characteristics of the baseflow recession based on the parameters and coefficients of the recession, and the shape of the individual recession curve and the master recession curve. The characteristics of the baseflow recession to research sub-watershed have the recession curves tend to sloped, describing the water storage well enough. The parameter Q0 (recession early), α and the recession constant Krb ranging from 0,80 – 0,90 for the individual and master recession curve in all three research sub-watershed. This calculation result indicates that the recession characteristics in three research sub-watershed have the condition of water storage is excellent, because they are supported by the aquifer characteristics dominated by the geological structures are more permeable (porous).